2016
DOI: 10.1590/s0004-28032016000100010
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between Helicobacter Pylori's Virulence and Increased Serum C-Reactive Protein Levels in Functional Dyspeptic Patients

Abstract: -Background -Recently, a great variety of studies aimed to investigate and even suggest Helicobacter pylori as an important key factor in gastrointestinal and non-gastrointestinal events development. The well-established relationship between bacterial virulence and increased risk for peptic ulcer or gastric carcinoma is not so clear when comparing inflammation markers alterations, such C-reactive protein, with the pathogen. Objective -The objective of this study was to evaluate the presence of H. pylori, bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
4
0
4
Order By: Relevance
“…This indicates that H. pylori infection is closely related to CRP values. Several previous studies have shown that the CRP value will decrease significantly in patients who have received H.pylori eradication therapy (Andreola, et al, 2016). In this study, it was reported that the mean CRP value in the H.pylori positive group was 36.78, and the mean CRP value in the H.pylori group.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…This indicates that H. pylori infection is closely related to CRP values. Several previous studies have shown that the CRP value will decrease significantly in patients who have received H.pylori eradication therapy (Andreola, et al, 2016). In this study, it was reported that the mean CRP value in the H.pylori positive group was 36.78, and the mean CRP value in the H.pylori group.…”
Section: Discussionmentioning
confidence: 49%
“…However, other studies have obtained different results. In a study conducted on 489 dyspeptic patients, it was found that the CRP value was higher in the positive H.pylori group than the negative H.pylori group, but there was no significant difference (p = 0.817) (Andreola, et al, 2016). The same thing was also reported in the study in 453 patients that CRP values were significantly higher in seropositive patients than in seronegative patients (Alimohammadin, et al, 2016).…”
Section: Discussionmentioning
confidence: 67%
“…In contrast to the Brazilian study, it was stated that there was no association between CRP levels and H. pylori infection in patients with functional dyspepsia, especially those who were Cag A positive (Andreolla et al, 2016). Research in Korea stated that H. pylori seropositivity was not associated with CRP levels.…”
Section: Discussionmentioning
confidence: 72%
“…Нelicobacter pylori (HР) -одна з найпоширеніших інфекцій, що спостерігається у близько 60,0 % загальної популяції, і частота інфікування постійно зростає. Патолоґічний вплив НР не обмежується шлунком і дванадцятипалою кишкою, а характеризується також екстраабдомінальними порушеннями, зокрема системним запаленням, яке вважається критичним компонентом атеросклерозу і чинником ризику ГКС [2,5,8].…”
Section: ужгородський національний університетunclassified
“…HP провокує запальні та імунні реакції як на локальному, так і на системному рівні. Можливий зв'язок НР і ГКС пояснюється, з одного боку, системним ефектом місцевого запалення слизової оболонки ґастродуоденальної зони, а з іншого -хронічною імунозапальною відповіддю із залученням у процес віддалених структур за рахунок прямих і непрямих механізмів [5]. Прямий вплив на судинну стінку включає безпосереднє ураження ендотелію циркулюючими ендотоксинами з виникненням дисфункції, спазму гладеньких м'язів і локального запалення, тоді як непрямий зумовлений збільшенням умісту медіаторів запалення, що виявляють прокоаґулянтний і атероґенний ефект, а також можуть бути причиною синтезу перехресних антитіл [9].…”
Section: ужгородський національний університетunclassified